Analysis Discount, Free Ongkir, COD toward Buying Decision Shopee Product Marketplace Alurwah Moslemwear Store: Shopee Users in Madiun - Setiawan, Hendra; Purwanto, Hari; Widya Wati, Elsa (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The purpose of this study is to examine the direct and indirect effects of discounts, free shipping, and cash on delivery (COD) on consumer choices. Shopee users in Madiun, specifically at the Alurwah Moslemwear store, were the subjects of the study. The research sample consisted of 385 respondents. This study used SmartPLS version 4.0 for quantitative data processing. The results show that COD significantly and positively influences consumer purchasing decisions. Free shipping and discounts have an insignificant and negative effect on consumer purchasing decisions. Furthermore, the results indicate that these variables also have a direct effect on purchasing decisions. These promotional strategies encourage consumers to complete transactions by reducing costs and perceived risks, thus increasing purchasing decisions. Furthermore, the results indicate that only one variable has a direct effect, indicating the purchasing decision process. The other variables do not affect purchasing decisions. This study highlights the importance for online sellers, especially on e-commerce platforms like Shopee, to offer cash on delivery (COD) services to increase purchasing decisions. Despite offering attractive discounts and free shipping options, the Alurwah Muslim Clothing Store must provide more attractive strategies for customers. Sales must prioritize these factors in their marketing strategy.